2021
DOI: 10.1007/s00170-021-06774-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of 450-808 nm diode lasers for efficient energy absorption during powder bed fusion of Ti6Al4V

Abstract: The additive manufacturing process selective laser melting (SLM) uses a powder bed fusion approach to fully melt layers of powdered metal and create 3D components. Current SLM systems are equipped with either single or multiple (up to four) high-power galvo-scanning infrared fibre laser sources operating at a fixed wavelength of 1064 nm. At this wavelength, a limited laser energy absorption takes place for most metals (e.g. alloys of aluminium have less than 10% absorption and titanium 50-60% absorption). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This is due to the lower heat conductivity of titanium compared with steel (~6 W/m∙K for Ti6Al4V [ 17 ] vs. ~18–24 for 316 steel [ 18 ]). On the other hand, it has a higher absorption coefficient for 1064 nm with respect to steel (~65% for Ti vs. 30% for iron [ 19 , 20 ]).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the lower heat conductivity of titanium compared with steel (~6 W/m∙K for Ti6Al4V [ 17 ] vs. ~18–24 for 316 steel [ 18 ]). On the other hand, it has a higher absorption coefficient for 1064 nm with respect to steel (~65% for Ti vs. 30% for iron [ 19 , 20 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The initial heating interval typically takes 0.2 ms. The occurrence of this interval is owing to the power rise time (0.05 ms, measured by the laser manufacturer) of the laser and the possible thin layer of oxidization on the substrate surface, knowing that the absorptivity of the 1064 nm laser of Titanium Oxide is less than 0.1 while the Ti–6Al–4V is over 60% 73 , 74 .
Figure 3 ( a – l ) The selected high-speed X-ray images of the melt pool of Trial #20.
…”
Section: Resultsmentioning
confidence: 99%
“…5 , 410 SS is harder to melt by the 1070 nm laser. This is because Ti–6Al–4V has a higher absorptivity at 1070 nm (60%) compared with steel (30%) 74 , 81 . Specifically, Trial #5 (410 SS, 130 W, 2 ms) has the same laser power as Trial #17 (Ti–6Al–4V, 130 W, 0.6 ms).…”
Section: Correlation Analysis and Ir-based Melt Pool Information Pred...mentioning
confidence: 99%
“…The results showed that due to the shorter wavelength of the diode laser (~808 nm) compared to Nd:YAG (~1064 nm), which leads to more absorption of laser energy, the diode laser produces a higher surface hardness, and also bigger depth and width of hardened zone than the Nd: YAG laser. Moreover, it creates more MHD depth and width than Nd: YAG laser [18]. However, scarce information related to this topic is available in the literature regarding metastable austenitic stainless steel (MASS) and, in particular, by using the Nd:YLF laser to conduct superficial texture and/or patterns at the superficial level [19].…”
Section: Introductionmentioning
confidence: 99%